Karakteristik Alat Tangkap Gurita Yang di Pakai Nelayan Secara Alami Dapat Melindungi Ekosistem Terumbu Karang di Kabupaten Simeulue - Roslimah Roslimah; Nelvia Mai Susanti; Mutlas Ade Putra; Amin Haris (Zoologi: Jurnal Ilmu Peternakan, Ilmu Perikanan, Ilmu Kedokteran Hewan, 2024)
The aim of this study was to assess the impact of octopus fishing gear use on coral reef ecosystems in Simeulue District. The research was conducted in May 2024, with research methods combining in-depth interviews and field observations. The results show that the use of unsustainable fishing gear, such as nets, contributes to the destruction of coral reefs, which negatively impacts marine biodiversity. Although fishers recognize the importance of ecosystem sustainability, challenges in adopting environmentally friendly practices still exist, including a lack of law enforcement and education. The conclusion of this study emphasizes the need for collaboration between the government and fishing communities in formulating more effective fisheries resource management policies, as well as the importance of training in sustainable fishing techniques. The study provides recommendations for the implementation of stricter regulations on the use of fishing gear, as well as encouraging active participation of fishers in fisheries resource management.